Probing the Limits of Ligand Steric Bulk: Backbone CH Activation in a Saturated N‐Heterocyclic Carbene. Issue 13 (24th February 2014) - Phillips, Nicholas; Tirfoin, Remi; Aldridge, Simon
Abstract The consequences of extremely high steric loading have been probed for late transition metal complexes featuring the expanded ring N‐heterocyclic carbene 6‐Dipp. The reluctance of this ligand to form 2:1 complexes with d‐block metals (rationalised on the basis of its percentage buried volume, % Vbur, of 50.8 %) leads to CH and CN bond activation processes driven by attack at the backbone β‐CH2 unit. In the presence of IrI (or indeed H+) the net result is the formation of an allyl formamidine fragment, while AuI brings about an additional ring (re‐)closure step via nucleophilic attack at the coordinated alkene. The net transformation of 6‐Dipp in the presence of [(6‐Dipp)Au]+ represents to our knowledge the first example of backbone CH activation of a saturated N‐heterocyclic carbene, proceeding in this case via a mechanism which involves free carbene in addition to the AuI centre.